Spatial and Temporal Dynamics of Dissolved Organic Carbon, Chlorophyll, Nutrients, and Trace Metals in Maritime Antarctic Snow and Snowmelt - Nowak, Aga; Hodson, Andy; Turchyn, Alexandra V. (Frontiers in Earth Science, 2018)
Despite scientific interest in the investigation of biogeochemical changes in meltwaters of the Antarctic Peninsula, we still lack an understanding of the seasonal dynamics and release of dissolved and particulate carbon, nutrients, as well as trace metals from Antarctic snowpacks. Harsh conditions, lack of appreciation of the heterogeneity of the environment, as well as logistical constraints during fieldwork mean there is great demand for more detailed and comprehensive research. Therefore, a unique, comprehensive study of snowpack biogeochemistry was performed in the Ryder Bay area of the Antarctic Peninsula during the entire 2016/2017 melt season. Two-hundred snowpack and snowmelt samples were collected throughout the campaign, to quantify for the first time, seasonal dynamics and export of dissolved carbon, in-vivo chlorophyll, nutrient and trace metals from Antarctic snowpack in various locations. Our study uncovered the importance of environmental heterogeneity with respect to the export of solutes and carbon. A distinctive split in the temporal dynamics of solute export was found, suggesting that some solutes are rapidly delivered to coastal environments early in the summer whilst others are delivered more gradually throughout it. Coastal, low elevation snowpacks were identified as “power plants” of microbial activity, playing an important role in the regulation of land-ocean fluxes of labile carbon and bio-limiting macro- and micro-nutrients. We also found that multiannual snow residing deep below the surface can further contribute to biogeochemical enrichment of coastal ecosystems. Additionally, inland snowpack have been identified as a store for nutrients, dissolved organic carbon and chlorophyll. Lastly, we show that a number of factors (environmental characteristics, geochemical heterogeneity and internal biogeochemical processes in snow) make simple snowpack surveys insufficient for the prediction of biogeochemical fluxes carried by snowmelt runoff into the marine environment. A return to significant fieldwork-based research in Antarctica is therefore necessary to advance our knowledge of the complex biogeochemical processes occurring there. This study therefore provides crucial data and process insights for more accurate predictions of how changing climate will influence the Antarctic carbon cycle and the globally important Southern Ocean ecosystem.